An International Study of Adherence to Guidelines for Patients Hospitalised with a COPD Exacerbation. (30th March 2017) - Seys, Deborah; Bruyneel, Luk; Decramer, Marc; Lodewijckx, Cathy; Panella, Massimiliano; Sermeus, Walter; Boto, Paulo; Vanhaecht, Kris
ABSTRACT : Guideline adherence rates for the treatment of chronic obstructive pulmonary disease (COPD) exacerbation are low. The aim of this study is to perform an importance-performance analysis as an approach for prioritisation of interventions by linking guidelines adherence rates to expert consensus rates for the in-hospital management of COPD exacerbation. We illustrate the relevance of such approach by describing variation in guideline adherence across indicators and hospitals. A secondary data analysis of patients with an acute COPD exacerbation admitted to Belgian, Italian and Portuguese hospitals was performed. Twenty-one process indicators were used to describe adherence to guidelines from patient record reviews. Expert consensus on the importance for follow-up of these 21 indicators was derived from a previous Delphi study. Three of the twenty-one indicators had high level of expert consensus and a high level of adherence. Eleven of the twenty-one indicators had high level of expert consensus but a low level of adherence. For none of the 378 patients included in this study were all process indicators adhered to, patients received 41.0% of the recommended care on average, and only 34.1% of the patients received 50% or more of the care they should receive. There was also a large variation within and between hospitals regarding the care received. This study confirms the findings of previous studies, indicating that COPD exacerbations are largely undertreated. Importance-performance analysis provides a decision-making tool for prioritising indicators. All hospitals in this study would benefit from having in place a quality framework for systematic follow-up of these indicators.